Recovery of Apraxia of Speech and Aphasia in Patients With Hand Motor Impairment After Stroke - Hybbinette, Helena; Schalling, Ellika; Plantin, Jeanette; Nygren-Deboussard, Catharina; Schütz, Marika; Östberg, Per; Lindberg, Påvel G. (Frontiers in Neurology, 2021)
Objective: Aphasia and apraxia of speech (AOS) after stroke frequently co-occur with a hand motor impairment but few studies have investigated stroke recovery across motor and speech-language domains. In this study, we set out to test the shared recovery hypothesis. We aimed to (1) describe the prevalence of AOS and aphasia in subacute stroke patients with a hand motor impairment and (2) to compare recovery across speech-language and hand motor domains. In addition, we also explored factors predicting recovery from AOS. Methods: Seventy participants with mild to severe upper extremity paresis were assessed; 50% of these (n=35) had left hemisphere (LH) lesions. Aphasia, AOS and hand motor assessments and magnetic resonance imaging were conducted at 4 weeks and at 6 months after stroke onset. Recovery was characterized in 15 participants showing initial aphasia that also had complete follow-up data at 6 months. Results: All participants with AOS and/or aphasia had LH lesions. In LH lesioned, the prevalence of aphasia was 71% and of AOS 57%. All participants with AOS had aphasia; 80% of the participants with aphasia also had AOS. Recovery in aphasia and AOS followed a parallel pattern to that observed in hand motor impairment and recovery correlated positively across speech-language and motor domains. The majority of participants with severe initial aphasia and AOS showed a limited but similar amount of recovery across domains. Lesion volume did not correlate with behavioral score results, nor with recovery. The initial aphasia score was the strongest predictor of AOS recovery. Conclusion: Our findings confirm the common occurrence of AOS and aphasia in LH stroke patients with a hand motor impairment. Recovery was similar across speech-language and motor domains, even in patients with severe impairment, supporting the shared recovery hypothesis and that similar brain recovery mechanisms are involved in speech-language and motor recovery. These observations contribute to the knowledge of AOS and its relation to motor and language functions and add information that may serve as a basis for future studies of post stroke recovery. Studies including neuroimaging or biological assays are required to gain further knowledge on shared brain recovery mechanisms.